Isolation and characterization of high tolerant yeast for co-utilization of glucose and xylose for ethanol And xylitol production (Funded Work) - A. RAJANI CHOWDARY; CH. PAVANA JYOTHI; REETHU NARAYANAN; B. SANTOSH KUMAR SANIVADA (International Journal of Pharma and Bio Sciences, 2017)
The present study was focused on isolating a high tolerant yeast strain capable of producing ethanol and xylitol using glucose and xylose as carbon source in yeast extract peptone media. Thirteen yeast strains were selected from 256 strains based on temperature, inhibitor and osmotolerance and further screened for ethanol and xylitol production with reference to six standard MTCC strains. Among all the strains, isolated Candida tropicalis CJ strain showed maximum production of ethanol (65%) from glucose and xylitol (60%) from xylose. High production stability of the strain was observed in temperature up to 420C and in wide range of pH and was able to ferment high concentration of sugars. Effect of various carbon and nitrogen sources was studied on the production of ethanol and xylitol. Among them urea and yeast extract served as efficient nitrogen sources and sucrose as efficient carbon source for maximum production of ethanol. Xylitol production was improved in the presence of de-oiled cake of coconut as nitrogen source and glucose as carbon source. In our study isolated strain C. tropicalis CJ was capable of showing integrated production of ethanol 75.40 % ±0.46 and xylitol 60.5%±0.51 simultaneously in Yeast Extract Peptone Dextrose xylose (YEPDX) medium at optimum agitation rate 200rpm. Simultaneous production of ethanol and xylitol, utilizing both the sugars glucose and xylose in the medium makes the process most economical and promising for the utilization of lignocellulosic substrates. The final product concentrations were significant and can be commercially applicable for large scale production of ethanol and xylitol.